THEATRE BETWEEN MANAUS AND PARINTINS: STAGES AND MEMORIES - Nascimento, Dilce Pio (Seven Editora, 2026)
This work investigates the production and reception of performing arts in Amazonas between the 1980s and the present day. The research originated from the cataloging of theatrical plays and sketches that, although fundamental to regional identity, were restricted to private collections. The objective is to examine the organization and re-signification of the documentary collection of Amazonian theatrical practices, analyzing how digital preservation and university extension, through projects such as Literature on Stage and LAMCEPIN (Amazonian Literature on Stage in the city of Parintins), combat cultural amnesia and assist in the training of teachers in Parintins. The temporal delimitation continues the studies of Costa and Azancoth (2010), expanding the focus to the interior of the state. Methodologically, this is a qualitative research based on documentary analysis and interviews (with preserved identities). The theoretical framework is based on Boal (2009), Colombo (1991), Derrida (2001), Freire (1996), and Tardif (2008). It concludes that integrating the collection into extension activities democratizes access to knowledge and strengthens the link between the university and the Amazonian community.